2021
DOI: 10.3389/fmicb.2021.683410
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metagenomic Assessment of Multiple Pre-harvest Control Points on Lettuce Resistomes at Field-Scale

Abstract: An integrated understanding of factors influencing the occurrence, distribution, and fate of antibiotic resistance genes (ARGs) in vegetable production systems is needed to inform the design and development of strategies for mitigating the potential for antibiotic resistance propagation in the food chain. The goal of the present study was to holistically track antibiotic resistance and associated microbiomes at three distinct pre-harvest control points in an agroecosystem in order to identify the potential imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…The greenhouse scale of the present study afforded examination of a wider array of factors, while comparing the portion of the experiment that was analogous to the field study afforded some degree of validation. Overall, the similarity of trends relative to those observed in the Wind et al (2021) study was striking. Notably, both studies reported relative abundance of total ARGs increasing from amendment to soil to both lettuce and radish when manure-derived amendments were applied.…”
Section: Comparison Of Greenhouse-and Field-scale Findingssupporting
confidence: 58%
See 1 more Smart Citation
“…The greenhouse scale of the present study afforded examination of a wider array of factors, while comparing the portion of the experiment that was analogous to the field study afforded some degree of validation. Overall, the similarity of trends relative to those observed in the Wind et al (2021) study was striking. Notably, both studies reported relative abundance of total ARGs increasing from amendment to soil to both lettuce and radish when manure-derived amendments were applied.…”
Section: Comparison Of Greenhouse-and Field-scale Findingssupporting
confidence: 58%
“…Overall, the similarity of trends relative to those observed in the Wind et al . (2021) study was striking. Notably, both studies reported relative abundance of total ARGs increasing from amendment to soil to both lettuce and radish when manure‐derived amendments were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomics outcompetes metabarcoding in that it provides insights into the metabolic, virulence or resistance potential of microbial communities. A good example is the study of Wind and colleagues ( Wind et al, 2021 ) focused on antibiotic resistance genes (ARG) across a vegetable production system. The study was interested on three pre-harvest “control-points,” i.e., manure and compost amendments, soils, and lettuce samples, to track antibiotic resistance and the associated microbiomes in order to identify the potential impacts of key agricultural management strategies.…”
Section: Meta-omics Approaches: Guidelines For and Applications To Th...mentioning
confidence: 99%
“…DNA fingerprinting and 16S DNA-based analyses were used to identify the harm of plant derived P. aeruginosa to humans and animals, which is complex and requires very professional inspectors ( Ambreetha et al, 2021 ). Biosensor method and 16r RNA gene amplicon sequencing, which had high detection efficiency, were used to analyze P. aeruginosa of food microorganisms, but these methods need complex pretreatment ( Zhong et al, 2020 ; Wind et al, 2021 ). Illumina whole gene sequencing has great advantages in accuracy, was used to analyze the distribution of P. aeruginosa after pasteurized milk, but it takes a lot of testing costs ( Maske et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%